PEMANFAATAN MEDIA PEMBELAJARAN GURU SOSIOLOGI KELAS X SMA NEGERI 1 SUNGAI RAYA - Fathoni, Muhammad Ihsan; Asriati, Nuraini; Sulistyarini, Sulistyarini (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research have purpose to see how far media learning is used by teacher especially in sociology subject in Sungai Raya Senior High School 1. Method which used in this research is descriptive method in form of qualitative research about media learningâ€™s utilization by sociology teacher in basic level of senior high school. The result of this research is utilization of leaning media especially in sociology subject in basic level still not optimal condition. This is related to some media like infocus need some preparation which wasting much time so in mostly time teacher rarely use this media in learning process. In the other side, in the school areas has been facillitated with wireless internet network which teoritically can support learning activities especially in sociology subject but this facility still indecent to do as it should be. That is because the lack network coverage to reach some point in the school .the other problem is related to the lack of student motivation and some caused by the lack of teacher abilities to maintain and organize learning activity in the class.Â Keywords : utilization in learning media,sociology teacher, sociology media learning